2013
DOI: 10.3109/07357907.2013.861473
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Human Mammaglobin Reduces Migration and Invasion of Breast Cancer Cells

Abstract: Little is known about the biological role of human mammaglobin (hMAM) that is considered as a promising marker for breast cancer. Here, we investigated hMAM's role related to migration and invasion of human breast cancer cells (hBCC). Compared to normal cells, hBCC have high MAM mRNA expression levels. Of the hBCC tested, MAM mRNA expression levels were higher in noninvasive than in invasive cells. Overexpression of hMAM in breast cancer cells decreased migration and invasion, whereas knockdown of hMAM increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…Similarly, the uteroglobin‐related protein (SCGB3A2) has demonstrated its potential as a growth factor in lung development . On the other hand, our results contradict those obtained from Eun–Ha Koh et al (2014) . The latter study demonstrates that recombinant over expression of MGB1 in the MB231 cell line leads to lower cell viability while siRNA‐mediated knock‐down of MGB1 has no effect.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Similarly, the uteroglobin‐related protein (SCGB3A2) has demonstrated its potential as a growth factor in lung development . On the other hand, our results contradict those obtained from Eun–Ha Koh et al (2014) . The latter study demonstrates that recombinant over expression of MGB1 in the MB231 cell line leads to lower cell viability while siRNA‐mediated knock‐down of MGB1 has no effect.…”
Section: Discussioncontrasting
confidence: 91%
“…We believe that technical variance and different study models may account for our divergent findings. Similar to Eun-Ha Koh et al (2014), we have also made use of siRNA to transiently knock-down MGB1 expression in MB231 and observed that despite a reduction of MGB1 transcripts, MGB1 protein levels remained unchanged in a transient transfection system. Hence, we developed stable cell clones with MGB1-specific shRNAs to carry out our functional characterization.…”
Section: Discussionmentioning
confidence: 79%
“…This was probably attributable to the detection of MGB derived from micrometastases of breast cancer, thus being indicative of late-stage disease. 47,48 Other studies reported that MGB up-regulation in breast cancer cell lines reduced cell migration and invasion, 24 and that its expression in primary breast cancers had favourable or absent prognostic implications. 9,22 In fact, MGB did not show consistent associations with other clinicopathological parameters, with some reported correlations with factors reflecting a less aggressive tumour phenotype, such as hormonal receptor positivity, low Ki67 index, low histological grade, and negative lymph nodes, [21][22][23] and another study not showing any correlation.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is expressed in 32-100% of breast cancers. 11,12 Despite their widespread use as diagnostic markers, their prognostic significance remains elusive, 6,7,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and this may be attributable to breast cancer heterogeneity. Tumours with different oestrogen receptor (ER) status and HER2 status are distinct entities with different prognoses and underlying biological characteristics, and are therefore associated with different risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers that are currently in use (or emerging biomarkers) for the early detection and prognosis of breast cancer include CA 15-3, tissue polypeptide-specific antigen (TPS), estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2), nm23 metastasis suppressor gene (NME), proliferating cell nuclear antigen (PCNA), human mammaglobin (hMAM), vascular endothelial growth factor (VEGF), Bcl-2, and p53 (Weigel and Dowsett, 2010;Koh et al, 2014). There are several risk factors that pose an increased risk of breast cancer, including age, diet, lifestyle, and genetics.…”
Section: Introductionmentioning
confidence: 99%